Osteomielitis en los maxilares, reporte de 25 casos - Francisco Levi Duque-Serna (Universidad de Antioquia, 1998)
In the present study, 25 patients were analyzed, whose ages were between 4-73 years old. Radiographic and histophatologicali studies confirmed the clinical diagnosis. In 80% of the infection was localized in the mandible and 20% in the maxillae. 72% of the patients presented at the initial examination an active fistulae, of these 56% were irztraoral and 16% extraoral. 64% of the cases were observed after dental extractions, of these, 36% were seen in the temporary teeth. 60% of the patients consulted only four months after the initial symptoms and signs appeared. The treatment consisted in the extraction of the affected teeth, with the exception of two of them that were treated endodontically. Also were used different types of antibiotics and the bone sequestrum was removed. In two cases ultrasound was used obtaininy excellent results.